Riau malay dance preservation strategies: a digital ethnographic study of Riau malay dance education and promotion practices on tiktok - Syefriani, Syefriani; Saearani, Muhammad Fazli Taib (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
In the era of globalization marked by the influence of foreign cultures, the Riau Malay dance, as a cultural heritage, is crucial to preserve ad the local cultural identity of the Riau community. This study aims to explore the tikTok application as an effective medium for educating and promoting the Riau Malay dance. The method employed in this research is digital ethnography with a qualitative approach, involving participatory observation of TikTok content as well as in-depth interviews with content creators engaged in the education and promotion of the Riau Malay dance. Data were analyzed to identify communication patterns, promotion strategies, and forms of digital interaction that strengthen awareness of locak cultural. The findings indicate that tikTok plays a significant role in disseminating information and increasing the participation of the younger generation on promoting the Riau Malay dance through educational and interactive content. The study also reveals collaboration among artists, educators, and content creators resulting in sustainable cultural innovation. However, challenges related to cultutral simplification and the dominance of entertainment content need to be managed to ensure that the authentic values of local culture are preserved. These findings contribute new insights into understanding the role of social media as a tool for local cultural education and offer strategic recommendations for the development of cultural promotion in the era digital, particularly concerning the Riau Malay dance.